Investigation of the Cross-talk Mechanism in Caco-2 Cells during Clostridium difficile Infection through Genetic-and-Epigenetic Interspecies Networks: Big Data Mining and Genome-Wide Identification - Li, Cheng-Wei; Su, Ming-He; Chen, Bor-Sen (Frontiers in Immunology, 2017)
Clostridium difficile is the leading cause of nosocomial antibiotic-associated diarrhea, and the major etiologic agent of pseudomembranous colitis. In severe cases, C. difficile infection (CDI) can cause toxic megacolon, intestinal perforation, and death. The intestinal epithelium is the first tissue encountered in the adhesion and colonization of C. difficile, and serves as a physical defense barrier against infection. Despite the well-characterized cytotoxicity, few studies have investigated the genome-wide interplay between host cells and C. difficile. The aim of this study is to investigate the genetic and epigenetic molecular mechanisms between human colorectal epithelial Caco-2 cells and C. difficile during the early (0–60 min) and late stages (30–120 min) of infection. To investigate the cross-talk mechanisms during the progression of infection, we introduced a systems biology approach using big data mining, dynamic network modeling, a genome-wide data identification method, system order detection scheme, and principal network projection method (PNP). We focused on the construction of genome-wide genetic-and-epigenetic interspecies networks (GEINs) and subsequent extraction of host-pathogen core networks (HPNs) to investigate the progression of underlying host/pathogen genetic and epigenetic mechanisms from the early to late stages of CDI. Based on our results, we suggest that the cell wall proteins CD2787 and CD0237, which both play an important role in cell adhesion and pathogen defense mechanisms, can be considered as potential drug targets. In addition, the crucial proteins employed by C. difficile for sporulation, including CD1214, CD2629, and CD2643, can also be considered as potential drug targets since spore-mediated re-infection is a critical issue.